Genetic variation and population genetic structure of Laodelphax striatellus via genome‐wide single nucleotide polymorphisms from specific‐locus amplified fragment‐sequencing. (28th December 2018) - Wang, Xingya; Lu, Bin; Shao, Lingyun; Yu, Fengquan; Zheng, Wenjing; Sun, Fuyu
Abstract: The small brown planthopper (SBPH), Laodelphax striatellus, is one of the most destructive agricultural pests that causes serious economic loss in the main rice‐producing areas of China. To clarify issues such as the genetic differentiation, gene flow and population genetic structure of SBPH populations, we investigated the genetic diversity, genetic structure and phylogeography of 27 SBPH populations at 23 sampling sites from three climatic zones of China using specific‐locus amplified fragment sequencing (SLAF‐seq) for large‐scale single nucleotide polymorphism (SNP) detection. In total, 115.95 M reads, 56, 355 polymorphic specific‐locus amplified fragments were developed, and 32, 556 reliable single nucleotides (SNPs) were detected. The results indicated that the genotypes of many polymorphism sites had low heterozygosity in every population. Overall, the pairwise F ST values between the populations varied from 0.056 to 0.092; it suggested the lack of strong differentiation among three climatic zone groups, respectively. It also suggested a strong level of gene flow (Nm) among populations in different climate zones, ranging from 28.864 to 35.197. Phylogenetic analyses, principal component analysis (PCA), Bayesian clustering method and AMOVA revealed that there was no evidence genetic clustering in three main bioclimatic zones. Neutrality testing provided strong evidence for a recent rapid expansion without any recent genetic bottleneck in these populations. Accordingly, the results of the present study should be beneficial for SBPH management and provide insight into the genetics of SBPH.